A SURPRISING TWIST: HYPONATREMIA INDUCED BY ZOLEDRONIC ACID – A RARE CLINICAL PUZZLE - Othman, Nurul Hayati; Jasmiad, Nurbadriah; Ismail, Shartiyah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Zoledronic acid is a potent bisphosphonate commonly used in the management of severe hypercalcemia, particularly in cases related to malignancy or metabolic bone disease. While hypocalcemia is a well-documented side effect following zoledronic acid administration especially in patients with primary hyperparathyroidism, there are no widely reported instances of hyponatremia in this patient population. We present a unique case of significant hyponatremia associated with zoledronic acid in a patient with primary hyperparathyroidism. CASE A 58-year-old female with a background of severe hypercalcemia secondary to primary hyperparathyroidism complicated by nephrocalcinosis and severe osteoporosis presented with recurrent hospital admissions due to severe hypercalcemic episodes. Over a two-month period, she received three doses of intravenous zoledronic acid infusion, followed by a single subcutaneous injection of denosumab. During follow-up in the clinic, laboratory investigations revealed significant hyponatremia (sodium: 113 mmol/L) and hypophosphatemia (phosphate: 0.52 mmol/L). There was no glycosuria, no hypokalemia, no hypouricemia and venous blood gas was not acidotic which excludes Fanconi syndrome. She was asymptomatic and denied any episode of vomiting or diarrhea. Secondary causes of adrenal insufficiency, syndrome of inappropriate antidiuretic hormone secretion (SIADH), hypothyroidism and diuretic use were excluded. With appropriate fluid management, her sodium levels gradually normalized. CONCLUSION This case highlights a rare but clinically significant adverse effect of zoledronic acid therapy. Hypocalcemia remains the more commonly expected metabolic complication. A few cases of hyponatremia associated with severe diarrhea or vomiting following zoledronic acid administration have been reported in the literature. However, our patient did not exhibit such gastrointestinal symptoms. Although the exact mechanism by which zoledronic acid contributes to hyponatremia remains unclear, early recognition is crucial to prevent potential complications.